FAKTOR-FAKTOR PENENTU PRODUKSI USAHATANI CABAI (Capsicum frutescens L - Wiwin P. Lona; Marthen R. Pellokila; Doppy R. Nendissa (Buletin Ilmiah Impas, 2021)
This study aims to compute the cayenne pepper (Capsicum frustescens, L.) farm’s income, and to determine factors that affecting production. Data collection by interviewing using a quertionnaire. Data analysing using the cobb-douglass production function model. The results showed that the total average cayenne pepper farm’s income at the study location was Rp 8.532.511 with a total average revenue of Rp 12.987.090 and the total average cost of Rp 4.454.578. Factors affecting production statistically were land and seed, however, fertilizer, pesticides, and labor were not. Simultaneously, land, seed, labor, fertilizer, and pesticides explained 98,1 percent of cayenne pepper’s production, and the rest were explained by variables that were not included in the model. Technically, cayenne pepper farm’s production was not efficient (IRS condition), however, economically efficient (R/C>1)